The evidence for the impact of policy on physical activity outcomes within the school setting: A systematic review - Woods, Catherine B; Volf, Kevin; Kelly, Liam; Casey, Blathin; Gelius, Peter; Messing, Sven; Forberger, Sarah; Lakerveld, Jeroen; Zukowska, Joanna; Bengoechea, Enrique García (Journal of Sport and Health Science, 2021)
Purpose Despite the well-established health benefits of physical activity (PA) for young people (aged 4–19 years), most do not meet PA guidelines. Policies that support PA in schools may be promising, but their impact on PA behavior is poorly understood. The aim of this systematic review is to ascertain the level and type of evidence reported in the international scientific literature for policies within the school setting that contribute directly or indirectly to increasing PA. Methods This systematic review is compliant with Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines. Six databases were searched using key concepts of policy, school, evaluation, and PA. Following title and abstract screening of 2323 studies, 25 progressed to data synthesis. Methodological quality was assessed using standardized tools, and the strength of the evidence of policy impact was described based on pre-determined codes: positive, negative, inconclusive, or untested statistically. Results Evidence emerged for 9 policy areas that had a direct or indirect effect on PA within the school setting. These were whole school PA policy, physical education, sport/extracurricular PA, classroom-based PA, active breaks, physical environment, shared use agreements, and active school transport and surveillance. The bulk of the evidence was significantly positive (54%), 27% was inconclusive, 9% was significantly negative, and 11% was untested (due to rounding, some numbers add to 99 or 101). Frequency of evidence was highest in the primary setting (41%), 34% in the secondary setting, and 24% in primary/secondary combined school settings. By policy area, frequency of evidence was highest for sport/extracurricular PA (35%), 17% for physical education PA, and 12% for whole school PA policy, with evidence for shared use agreements between schools and local communities rarely reported (2%). Comparing relative strength of evidence, the evidence for shared use agreements, though sparse, was 100% positive, 60% of the evidence for whole school PA policy was positive, 59% of the evidence for sport/extracurricular PA was positive, 57% of the evidence for physical education was positive, and 50% of the evidence for PA in classroom and for active breaks/recess was positive. Conclusion The current evidence base supports the effectiveness of PA policy actions within the school setting but cautions against a “one-size fits all” approach and emphasizes the need to examine policy implementation to maximize translation into practice. Greater clarity regarding terminology, measurement, and methods for evaluation of policy interventions is needed.<br
Keywords: Evaluation; Physical activity; Policy; Schools; Systematic review